The Relationship of Ns1 Antigen Profi Le and Days of Illness in Children with Dengue Virus Infection - Dwiyanti Puspitasari; Saraswati Dewi; Aryati Aryati (Jurnal Ners, 2013)
Introduction: Dengue NS1 Antigen (NS1 Ag) detection or quantification has become a specific diagnostic tool for dengue virus infection, but has variable sensitivity. Previous research reported NS1 Ag level can be detected up to the 7th–10th day of fever, others stated the sensitivity was decreased after four days of fever. We performed this research to analyze the NS1 Ag profile and its relationship with the day of illness.Methods: This study was a prospective cohort study on 39 children hospitalized at Dr. Soetomo Hospital Surabaya since November 2009 to May 2010. Inclusion criteria were acute fever less than 72 hours, bleeding tendency denoted at least by positive tourniquet test, age between 1–14 years, and confirmed by positive dengue IgM/IgG on the 5th day of fever. We performed daily quantitative dengue NS1 Ag tests until defervescence day, and its relationship with the day of illness were analyzed.Results: NS1 Ag was positive in 19/39 samples. Secondary infection occurred in 14/19 of Dengue Fever and 17/20 of Dengue Hemorrhagic Fever cases. Positivity of NS1Ag was higher in primary (6/8 cases) than secondary infection (12/31 cases). Mean level of NS1 Ag was highest on the 2nd day, decreased afterwards and undetected on the 5th day of fever. There was significant relationship between NS1 Ag positivity (P=0.037, rs=-0.9) and level (P<0.001, rs=-1) with the day of illness.Conclusion: Dengue NS1 Ag positivity and level were highest during the acute phase of fever and decreased afterwards.The Relationship of Ns1 Antigen Profi Le and Days of Illness in Children with Dengue Virus Infection